Exploring time-killing and biofilm inhibition potential of bioactive proteins extracted from two varieties of Pleurotus ostreatus - Gangwar, Reena; Salem, Mohamed M.; Maurya, Vineet Kumar; Bekhit, Mounir M.; Singh, Nisha; Amara, Amro Abd Al Fattah; Sahu, Ram Kumar; Ibrahim, Mohamed A. (Frontiers in Microbiology, 2024)
Introduction Dental caries, caused by oral microbial pathogens, are a global health concern, further exacerbated by the presence of methicillin-resistant Staphylococcus aureus (MRSA). Bioactive proteins and peptides (BAPs) exhibit potent antimicrobial properties, targeting multiple cellular mechanisms within pathogens, reducing the likelihood of resistance development. Given the antimicrobial potential of BAPs, this study aimed to compare the efficacy of BAPs extracted from cultivated (Pleurotus ostreatus, PoC) and wild (Pleurotus ostreatus, PoW) mushrooms against pathogens responsible for dental caries. Methods BAPs were extracted from both PoC and PoW using a TCA-acetone method. Antimicrobial activities were tested against seven bacteria and one fungus using agar well diffusion and MIC determination. Antibiofilm activity was assessed via modified CV assay, while DPPH and erythrocyte lysis tests evaluated free radical scavenging. Results PoC showed superior antimicrobial efficacy, with lower MIC and MBC values, and disrupted biofilm integrity at increasing concentrations. PoW exhibited better antioxidant activity with higher DPPH scavenging, though its antimicrobial efficacy was slightly lower than PoC. Discussion Both PoC and PoW BAPs inhibited dental pathogens, with PoC showing stronger inhibition against MRSA and nystatin-resistant Candida albicans. This suggests BAPs may target additional cellular mechanisms beyond membranes, PBPs, and ergosterols. Despite PoW’s stronger antioxidant properties, both BAPs had comparable antibiofilm activity. These findings suggest complementary actions of BAPs from PoC and PoW both, in treating dental caries, offering broad-spectrum antimicrobial and antioxidant benefits.